Maria W. Stewart and the Roots of Black Political Thought - Waters, Kristin (Book collections on Project MUSE., 2022)
"Maria W. Stewart and the Roots of Black Political Thought tells a crucial, almost-forgotten story of African Americans of early nineteenth-century America. In 1833, Maria Stewart (1803-1879) told a gathering at the African Masonic Hall on Boston's Beacon Hill: 'African rights and liberty is a subject that ought to fire the breast of every free man of color in these United States.' She exhorted her audience to embrace the idea that the founding principles of the nation must extend to people of color. Otherwise those truths are merely the hypocritical expression of an ungodly white power, a travesty of original democratic ideals. Like her mentor, David Walker, Stewart illustrated the practical inconsistencies of classical liberalism as enacted in the US and delivered a call to action for ending racism and addressing gender discrimination. Between 1831 and 1833, Stewart's intellectual productions, as she called them, ranged across topics from true emancipation for African Americans, the Black convention movement, the hypocrisy of white Christianity, Black liberation theology, and gender inequity. Along with Walker's Appeal to the Coloured Citizens of the World, her body of work constitutes a significant foundation for a moral and political theory that is finding new resonance today--Insurrectionist Ethics. In this work of recovery, author Kristin Waters examines the roots of Black political activism in the petition movement, Prince Hall and the creation of the first Black masonic lodges, the Black Baptist movement spearheaded by the brothers Thomas, Benjamin, and Nathaniel Paul, writings, sermons, and the practices of festival days, through the story of this remarkable but largely unheralded woman and pioneering public intellectual"--